Jaringan 5G dengan Parameter SINR, RSRP, dan Throughput - Nabil Fajri; Yulindon Yulindon (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study provides a literature review on 5G New Radio (NR) performance, focusing on three key physical layer parameters: Reference Signal Received Power (RSRP), Signal-to-Interference-plus-Noise Ratio (SINR), and Throughput. By synthesizing 15 research papers from 2015–2026, the analysis reveals that SINR is the most critical predictor of throughput, with a strong correlation coefficient of 0.85. The findings highlight that while RSRP ensures coverage, SINR determines the actual data rate, which varies significantly across urban, industrial, and highway environments. The study identifies research gaps in KPI threshold standardization and the comparative performance of 5G Standalone (SA) versus Non-Standalone (NSA) architectures.